2015
DOI: 10.1111/jdv.13239
|View full text |Cite
|
Sign up to set email alerts
|

Fixed, low radiant exposure vs. incremental radiant exposure approach for diode laser hair reduction: a randomized, split axilla, comparative single‐blinded trial

Abstract: Both low and incremental radiant exposures produced similar hair reduction and high and comparable patient satisfaction. However, low radiant exposure diode laser treatments were less painful and better tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This study reports unique aspects of diode laser 805 nm hair removal safety in a mixed-race group of patients and no similar study is found among available references. Available references report that hair removal using diode laser is safe and effective in all skin types according to Fitzpatrick scale, as shown in studies of Cameron et al, 1 Pavlović et al 11 and Fayne et al 2 ; however no study was made in accordance to mixed race patients. In this study, investigators achieved excellent results in pubic area in a group of mixed race patients in objective 86, 90% and subjective 84, 40% assessments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study reports unique aspects of diode laser 805 nm hair removal safety in a mixed-race group of patients and no similar study is found among available references. Available references report that hair removal using diode laser is safe and effective in all skin types according to Fitzpatrick scale, as shown in studies of Cameron et al, 1 Pavlović et al 11 and Fayne et al 2 ; however no study was made in accordance to mixed race patients. In this study, investigators achieved excellent results in pubic area in a group of mixed race patients in objective 86, 90% and subjective 84, 40% assessments.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] The available literature describes the effectiveness of the diode laser as a method for all skin types according to the Fitzpatrick scale hair removal, but the question of patient safety and minimization of side effects and postoperative complications in mixed-race patients remains unanswered. [1][2][3][7][8][9][10][11][12][13][14] In diode laser, the hair removal principle of selective photothermolysis applies where the chromophore is melanin in the hair shaft itself and the bulge. However, the same chromophore can be found as skin pigment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hair reduction of 30%-50% was reported in research. 1 It is well known that despite its widely reported effectiveness, [2][3][4][5][6][7][8] there are certain side effects and unconfirmed adverse effects related to this treatment. 9,10 Patients who undergo laser hair reduction procedures may expect skin irritation, erythema, edema, postoperative Diode Laser 805 -Side Effects hypersensitivity and possible burns manifested by blisters and scabs.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, patients who decide to do pubic area hair removal more often choose the methods which give permanent results [8,12,[17][18][19]. To achieve that, photo epilation treatment is introduced on the basis of selective thermolysis with the use of various lasers with a specified light wavelength: ruby (694 nm), alexandrite (755 nm), diode (805, 810 nm), Nd:YAG (1064 nm) and incoherent xenon light -IPL (Intense Pulse Light) with the wave range between 590 and 1200 nm, described in literature as permanent methods of hair reduction [2,3,6,7,14,[18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%